2002
DOI: 10.1046/j.1365-201x.2002.00988.x
|View full text |Cite
|
Sign up to set email alerts
|

Nandrolone decanoate treatment induces changes in contractile responses of rat untrained fast‐twitch skeletal muscle

Abstract: This investigation was designed to examine whether short-term administration of anabolic-androgenic steroids (AAS) (nandrolone decanoate) could produce changes in contractile responses of untrained rat fast- (edl) and slow- (soleus) twitch skeletal muscle. Twenty male rats were divided into two groups, one group received weekly (for 6 weeks) an intramuscular injection of AAS, nandrolone decanoate (15 mg kg(-1)) and the second group received weekly the similar doses of vehicle (sterile peanut oil). In edl intac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
15
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 25 publications
6
15
0
Order By: Relevance
“…Our data are in agreement with recent studies demonstrating that drug treatment produces changes in 146 K-contracture of isolated sedentary rat edl and soleus cells associated with a shift to more negative potential of voltage-dependent activation without a change in the time constant of contracture relaxation [27].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Our data are in agreement with recent studies demonstrating that drug treatment produces changes in 146 K-contracture of isolated sedentary rat edl and soleus cells associated with a shift to more negative potential of voltage-dependent activation without a change in the time constant of contracture relaxation [27].…”
Section: Discussionsupporting
confidence: 83%
“…This proposal is in line with recent reports showing that the administration of nandrolone decanoate to sedentary animals results in alterations in the excitation-contraction coupling mechanism at the cellular level [16,27] and produces different changes in the contractile responses developed by fast and slow muscles.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…It is assumed that the K ϩ contracture amplitude depends on activation of the voltage sensor in the transverse tubule membrane, and that relaxation depends on inactivation of the process regulating calcium release from the sarcoplasmic reticulum and the ability of the sarcoplasmic reticulum to pump calcium [28]. We have recently found [27] that, in edl, nandrolone decanoate treatment induces an increase in K ϩ contracture tension that could be accounted for by a shift in the voltage-dependent activation and inactivation curve to more negative membrane potential Persistent Effects of Anabolic Steroids values, which became similar to soleus. Thus, it was proposed that, in contrast to soleus where a delayed potentiating of K ϩ contracture was found, in edl, the effect on K ϩ contracture tension due to hormone treatment was reversible after ending treatment.…”
Section: Caffeine Contracturesmentioning
confidence: 99%
“…Thus, it seems reasonable to suggest that nandrolone decanoate could alter one or more of these events such that force production is increased. We have recently shown that a short period of nandrolone decanoate treatment in untrained rat produces more pronounced changes in the contractile responses of edl than of soleus muscles by acting on the voltage dependency of activation and inactivation of contraction and on the sensitivity of contractile proteins without change in the MHC isoforms to Ca 2ϩ [27]. Therefore, we proposed that the absence of a significant difference between twitch tension of treated (5 wk of drug treatment followed by 5 wk of arrest) and control animals was associated with a reversible effect on the voltage dependency of activation and inactivation of contraction and on the sensitivity of contractile proteins to Ca 2ϩ .…”
Section: Caffeine Contracturesmentioning
confidence: 99%